2022
DOI: 10.3390/antiox11071366
|View full text |Cite
|
Sign up to set email alerts
|

How Aging and Oxidative Stress Influence the Cytopathic and Inflammatory Effects of SARS-CoV-2 Infection: The Role of Cellular Glutathione and Cysteine Metabolism

Abstract: SARS-CoV-2 infection can cause a severe respiratory distress syndrome with inflammatory and thrombotic complications, the severity of which increases with patients’ age and presence of comorbidity. The reasons for an age-dependent increase in the risk of severe COVID-19 could be many. These include defects in the homeostatic processes that control the cellular redox and its pivotal role in sustaining the immuno-inflammatory response to the host and the protection against oxidative stress and tissue degeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 87 publications
0
20
1
2
Order By: Relevance
“…NAFLD is related to increased oxidative stress, even in early stages of the disease [ 39 ]. On the other hand, oxidative stress is a risk factor for COVID-19 infection [ 40 ]. However, some authors have shown that oxidative stress was reduced due to confinement, as exposure to urban pollutants was reduced [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is related to increased oxidative stress, even in early stages of the disease [ 39 ]. On the other hand, oxidative stress is a risk factor for COVID-19 infection [ 40 ]. However, some authors have shown that oxidative stress was reduced due to confinement, as exposure to urban pollutants was reduced [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations of the thiol–disulfide redox balance in the lung tissue and lining fluids promotes the risk of infection and lowers the host’s ability to react to pathogens and hamper complications. 365 …”
Section: Critical Conclusion and Future Prospectsmentioning
confidence: 99%
“… 66 In the context of viral pathology, mainly during the first stages, there is an increased cysteine uptake to sustain viral replication, while the enhanced viral protein synthesis leads to thiol depletion and oxidative stress activation. 365 The corresponding oxidized form, cysteine disulfide, at concentrations higher than 300 μM in the elderly, is associated with an increased cardiovascular risk, 373 a condition tightly linked to COVID-19 severity. Benefits imparted by GlyNAC supplementation encompass: amelioration of glutathione deficiency, of glycine and cysteine profile, control on oxidative stress and inflammation, and correction of mitochondrial, endothelial vascular dysfunction, and insulin resistance, as proved in human clinical trials.…”
Section: Critical Conclusion and Future Prospectsmentioning
confidence: 99%
See 2 more Smart Citations